Szpital parafialny i przytułek w Garbowie - Makarewicz, Renata (Archiwa, Biblioteki i Muzea Kościelne, 2015)
Into duties of parish priests not only a ministry was written down, but also organising the care for old, ill, poor and skipped parishioners. After the Trent Council which was held in latach1545-1563, they started forming parish hospitals, and on the XIX turning point and the 20th century shelters and houses of the refuge were made. Into the history of the parish of Garbów activity of two protective institutions became part of: of the parish hospital and of the shelter called the Hostel for Old Men in Garbów. The article is aimed portraying of the history these two institutions, from which every for many years served for the Garbów communities. The first part of the article is regarding activity of the parish hospital. Based on observed parish and archival records and the available literature on the subject they presented here the standard of living of charges and funds of the hospital, and also to show the state of the residential building and ways of taking care of residents. Later an issue was introduced the foundation of hospital and other forms of financial supporting of hospitals. In the second part of the article based on parish records and numerous memory articles placed in the local Press they portrayed history of the coming into existence and functioning of the shelter which was assigned for the poorest group the Garbów communities. They described the case of purchasing the building and adapting it at residential target and involving landowners in the matter of creating the shelter. They presented a living conditions of residents and duties of nuns which worked at this institution, and ways of financing activity of the nursing home were shown.